Potensi Fitoplankton sebagai Sumber Daya Pakan pada Pemeliharaan Larva Ikan Mas (Cyprinus carpio) di BBPBAT Sukabumi - Ana Widiana; Astuti Kusumorini; Selvi Handayani (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
The main problem encountered in producing larvae is the larvae that got low due to high mortality. One attempt to overcome this problem is the use of phytoplankton as natural feed. The purpose of this study is to determine phytoplankton community structure and potential as a resource phytoplankton feed on larval rearing carp. The research was conducted in April 2012. The results showed that the phytoplankton found in the larval rearing pond goldfish are Class Bacillariophyceae (1 genera), Chlorophyceae (13 genera), and Cyanophyceae (7 genera). Phytoplankton Chlorophyceae group is a group that has the highest abundance of larval rearing carp pond. Diversity index of phytoplankton in pond carp larvae ranged from 0.65 to 1.64 (Low Diversity). Based on the preponderance index carp larvae utilize phytoplankton as natural feed by selecting the class Chlorophyceae and Cyanophyceaea in early growth until the time nursery a preponderance index value respectively 87.76% and 12.23%.